2015
DOI: 10.1111/ajd.12286
|View full text |Cite
|
Sign up to set email alerts
|

Eyelid sporotrichosis: Unique clinical findings in 72 patients

Abstract: Sporotrichosis on the eyelids is uncommon and has been rarely reported. As the largest series of 72 adults and children with eyelid sporotrichosis from Jilin ̀P̀̀rovince in China, this study provides useful information for the improved diagnosis and treatment of sporotrichosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(37 citation statements)
references
References 15 publications
(15 reference statements)
0
36
0
1
Order By: Relevance
“…1 Most reports on sporotrichosis cases originate from South American 2-7 and Asian countries. [8][9][10][11] Sporotrichosis is endemic in Jilin Province of Northeast China, especially in rural areas, and studies conducted in our department suggest that incidence is increasing. Specifically, the Department of Dermatology and Venerology at the First Hospital of Jilin University in Changchun (the setting of this study) reported 226 cases of sporotrichosis between 1987 and 2004 12 ; this compares with 457 cases diagnosed between 2007 and 2009.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…1 Most reports on sporotrichosis cases originate from South American 2-7 and Asian countries. [8][9][10][11] Sporotrichosis is endemic in Jilin Province of Northeast China, especially in rural areas, and studies conducted in our department suggest that incidence is increasing. Specifically, the Department of Dermatology and Venerology at the First Hospital of Jilin University in Changchun (the setting of this study) reported 226 cases of sporotrichosis between 1987 and 2004 12 ; this compares with 457 cases diagnosed between 2007 and 2009.…”
mentioning
confidence: 74%
“…The fungus is saprophytic, and humans are commonly infected during outdoor activities such as farming or gardening, when they are exposed to conidia on sphagnum moss, soil and decaying plant matter . Most reports on sporotrichosis cases originate from South American and Asian countries . Sporotrichosis is endemic in Jilin Province of Northeast China, especially in rural areas, and studies conducted in our department suggest that incidence is increasing.…”
Section: Introductionmentioning
confidence: 87%
“…and S. schenckii ) . To date, there has been increased recognition of this condition as more pediatric cases have been reported . Herein, we describe a new case of palpebral sporotrichosis in a 6‐year‐old child in the hyperendemic area of Abancay, Peru.…”
mentioning
confidence: 93%
“…Sporotrichosis in ocular adnexa is often associated with children <15 years of age, and in 82% of these cases, the disease is limited to the eyelids . Cases of palpebral sporotrichosis have been increasingly reported in endemic areas, such as Abancay in Peru, and China …”
mentioning
confidence: 99%
“…Traumatic inoculation is the most common mode of transmission, and spread from infected cats has been reported 1. Cases of sporotrichosis involving ocular adnexa are more common in younger patients, particularly children, who are thought to have greater exposure owing to contact with cats and playing in crop fields 23…”
mentioning
confidence: 99%